Richard Jewell [videorecording (DVD)] - Brenner, Marie; Wilde, Olivia; Rockwell, Sam; Hamm, Jon, 1971- (Warner Home Video, 2020)
The world is first introduced to Richard Jewell as the security guard who reports finding the device at the 1996 Atlanta bombing, his report making him a hero whose swift actions save countless lives. But within days, the law enforcement wannabe becomes the FBI's number one suspect, vilified by press and public alike, and his life ripped apart. Reaching out to independent, anti-establishment attorney Watson Bryant, Jewell staunchly professes his innocence.